Respuestas
Respuesta dada por:
0
Factorizar.
Caso.
Diferencia de cuadrados.
Aplicas.
a² - b² = (a + b)(a - b)
x² - y² =
(x + y)(x - y)
a² - 4 =
a² - 2² =
(a + 2)(a - 2)
1 - m² =
1² - m² =
(1 + m)(1 - m)
a² - 25 =
a² - 5² =
(a + 5)(a - 5)
4a² - 9 =
2²a² - 3² =
(2a + 3)(2a - 3)
a²b⁸ - c² =
a²(b⁴)² - c² =
(ab⁴ + c)(ab⁴ - c)
a¹⁰ - 49b¹² =
(a⁵)² - 7²(b⁶)² =
(a⁵ + 7b⁶)(a⁵ - 7b⁶)
Caso.
Diferencia de cuadrados.
Aplicas.
a² - b² = (a + b)(a - b)
x² - y² =
(x + y)(x - y)
a² - 4 =
a² - 2² =
(a + 2)(a - 2)
1 - m² =
1² - m² =
(1 + m)(1 - m)
a² - 25 =
a² - 5² =
(a + 5)(a - 5)
4a² - 9 =
2²a² - 3² =
(2a + 3)(2a - 3)
a²b⁸ - c² =
a²(b⁴)² - c² =
(ab⁴ + c)(ab⁴ - c)
a¹⁰ - 49b¹² =
(a⁵)² - 7²(b⁶)² =
(a⁵ + 7b⁶)(a⁵ - 7b⁶)
Respuesta dada por:
2
x² - y² = (x+y)(x-y)
a² - 4 = (a+2)(a-2)
1 - m² = (1+m)(1-m)
a² - 25 = (a+5)(a-5)
4a² - 9 = (2a+3)(2a-3)
![a^{2}b^{8} - c^{2} = (ab^{4} +c)(ab^{4}-c) a^{2}b^{8} - c^{2} = (ab^{4} +c)(ab^{4}-c)](https://tex.z-dn.net/?f=+a%5E%7B2%7Db%5E%7B8%7D+-++c%5E%7B2%7D+%3D+%28ab%5E%7B4%7D+%2Bc%29%28ab%5E%7B4%7D-c%29+++)
![a^{10} - 49 b^{12} = ( a^{5} +7 b^{6}) ( a^{5} -7 b^{6}) a^{10} - 49 b^{12} = ( a^{5} +7 b^{6}) ( a^{5} -7 b^{6})](https://tex.z-dn.net/?f=a%5E%7B10%7D++-+49+b%5E%7B12%7D+%3D+%28+a%5E%7B5%7D+%2B7+b%5E%7B6%7D%29+%28+a%5E%7B5%7D+-7+b%5E%7B6%7D%29)
a² - 4 = (a+2)(a-2)
1 - m² = (1+m)(1-m)
a² - 25 = (a+5)(a-5)
4a² - 9 = (2a+3)(2a-3)
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años